Donor diabetes mellitus is a risk factor for diminished outcome after liver transplantation: a nationwide retrospective cohort study. (5th November 2020) - Brüggenwirth, Isabel M.A.; van Reeven, Marjolein; Vasiliauskaitė, Indrė; van der Helm, Danny; van Hoek, Bart; Schaapherder, Alexander F.; Alwayn, Ian P.J.; van den Berg, Aad P.; de Meijer, Vincent E.; Darwish Murad, Sarwa; Polak, Wojciech G.; Porte, Robert J.
Summary: With the growing incidence of diabetes mellitus (DM), an increasing number of organ donors with DM can be expected. We sought to investigate the association between donor DM with early post‐transplant outcomes. From a national cohort of adult liver transplant recipients (1996–2016), all recipients transplanted with a liver from a DM donor ( n  = 69) were matched 1:2 with recipients of livers from non‐DM donors ( n  = 138). The primary end‐point included early post‐transplant outcome, such as the incidence of primary nonfunction (PNF), hepatic artery thrombosis (HAT), and 90‐day graft survival. Cox regression analysis was used to analyze the impact of donor DM on graft failure. PNF was observed in 5.8% of grafts from DM donors versus 2.9% of non‐DM donor grafts ( P  = 0.31). Recipients of grafts derived from DM donors had a higher incidence of HAT (8.7% vs. 2.2%, P  = 0.03) and decreased 90‐day graft survival (88.4% [70.9–91.1] vs. 96.4% [89.6–97.8], P  = 0.03) compared to recipients of grafts from non‐DM donors. The adjusted hazard ratio for donor DM on graft survival was 2.21 (1.08–4.53, P  = 0.03). In conclusion, donor DM is associated with diminished outcome early after liver transplantation. The increased incidence of HAT after transplantation of livers from DM donors requires further research.